IDENTIFIKASI FAKTOR-FAKTOR PENGHAMBAT PENERAPAN ANALISIS STANDAR BELANJA (ASB) DI PEMERINTAH KOTA MALANG - Sulaiman Maharshiyam (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2015)
It is known that by implementing the Expenditure Standard Analysis (ASB), the fairness of activities costs could be known and analysed. Malang City Government has not implemented ASB as a budgeting tool. This qualitative descriptive research aims to identify the impediment factors of why the ASB has not yet been implemented by Malang City Government as well as to know the efforts of Malang City Government to implement the ASB. Data collection is conducted through 3 methods which are observation, interview, and documentation. The result shows that there are several impediment factors that makes ASB has not been implemented yet in Malang City Government. There are 3 impediment factors, namely: (1) incomplete regulation, (2) lack of human resource competence, and (3) lack of coordination among stakeholder. The regulations do not regulate the ASB format, as the National Government nor the Malang City Government do not specifically concern about the ASB format. The quality of human resources of Malang City is considered to be low and lack of competence to arrange ASB because of lack of regeneration and lack of socialization and training about ASB. Good coordination among stakeholders is needed during budgeting process, however it does not work effectively. Coordination between service offices (dinas), City Government, Local Legislative, and Province Government is already good, but the coordination with the ministry and the National Government is needed to improve.Keywords: Expenditure Standard Analysis, ASB, Impediment Factors, Regional Financial Management, City Government, Budgeting, Regional Expenditure.